Coupled Model Transformations for QoS Enabled Component-Based Software Design (2008)
This thesis presents the Palladio Component Model and its accompanying transformations for component-based software design with predictable performance attributes. The use of transformations results in a deterministic relationship between the model and its implementation. The introduced Coupled Transformations method uses this relationship to include implementation details into predictions to get better predictions. The approach is validated in several case studies showing the increased accuracy.